Contributions of Health Care Coalitions to Preparedness and Resilience: Perspectives From Hospital Preparedness Program and Health Care Preparedness Coalitions. (6th November 2015) - Acosta, Joie; Howard, Stefanie; Chandra, Anita; Varda, Danielle; Sprong, Sara; Uscher-Pines, Lori
ABSTRACT: Objective: The purpose of this article was to describe how the Hospital Preparedness Program (HPP) and other health care coalitions conceptualize and measure progress or success and to identify strategies to improve coalition success and address known barriers to success. Methods: We conducted a structured literature review and interviews with key leaders from 22 HPPs and other coalitions. Interview transcripts were analyzed by using constant comparative analysis. Results: Five dimensions of coalition success were identified: strong member participation, diversity of members, positive changes in members' capacity to respond to or recover from disaster, sharing of resources among members, and being perceived as a trendsetter. Common barriers to success were also identified (eg, a lack of funding and staff). To address these barriers, coalitions suggested a range of mitigation strategies (eg, establishing formal memoranda of agreement). Both dimensions of and barriers to coalition success varied by coalition type. Conclusions: Currently, the term health care coalition is a one-size-fits-all term. In reality, this umbrella term describes a variety of different configurations, member bodies, and capabilities. The analysis offered a typology to categorize health care coalitions by primary function during a disaster response. Developing a common typology that could be used to specify capabilities or functions of coalitions may be helpful to advancing their development. ( Disaster Med Public Health Preparedness . 2015;9:690–697)